IMPROVING STUDENTS' ENGLISH VOCABULARY THROUGH THE MEDIA ANIMATION FILM 'JACK AND THE GIANT BEAN TREE' - Endah Sulistianingwarni; Suryadi Suryadi (PROJECT (Professional Journal of English Education), 2023)
This study aims to determine the effect of the animated film media "Jack and the giant bean tree" on improving the English vocabulary of seventh grade students of SMPN 5 Serang City. This research is an experimental research with one group pretest and posttest design. The population in this study was the seventh grade students of SMPN 5 Serang City which consisted of 10 classes, each class had 30 students with a total of 300 students, but from ten classes that were randomly selected as samples in this study were class VII B which amounted to 30 student. Data analysis in this study used the t test. The results of this study indicate that there is an influence of the animated film media "Jack and the giant nuts tree" on students' English vocabulary, with t count 8.939 > t table 2.042, from pre-test data it has an average value of 50.00 and from post-test data has an average value of 80.00. The difference in the average value of 30.00 with a percentage increase of 60% indicates the extent to which the change in the expansion of students' English vocabulary. Based on these results, it can be concluded that the use of animated film media "Jack and the giant bean tree" has an effect on increasing the English vocabulary of class VII B students of SMPN 5 Serang City. Keywords:  English Vocabulary; Media Animation; Jack and The Giant Bean Tree